2002
DOI: 10.1093/intimm/dxf112
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Na,K-ATPase beta3 subunit by a specific mAb suppresses T and B lymphocyte activation

Abstract: In order to identify new molecules involved in regulation of T cell proliferation, we generated various mAb by immunization of mice with the T cell line Molt4. We found one mAb (termed P-3E10) that down-regulated the in vitro T cell proliferation induced by CD3-specific OKT3 mAb. The P-3E10 mAb was also able to inhibit IFN-gamma, IL-2, IL-4 and IL-10 production of OKT3-activated T cells. The antigen recognized by P-3E10 mAb is broadly expressed on all hematopoietic as well as on all non-hematopoietic cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…However, a monoclonal antibody specific for the β3 subunit of the Na,K-ATPase inhibits mitogen activation of both T- and B-lymphocytes (62). Another interesting protein identified by SPPLAT was Evi2a.…”
Section: Discussionmentioning
confidence: 99%
“…However, a monoclonal antibody specific for the β3 subunit of the Na,K-ATPase inhibits mitogen activation of both T- and B-lymphocytes (62). Another interesting protein identified by SPPLAT was Evi2a.…”
Section: Discussionmentioning
confidence: 99%
“…The reported reduction of the β2 isoform in glioblastomas is interesting because this could be the factor that initiates invasion by these cells [42]. Inactivation of the β3 isoform can inactivate T and B lymphocytes, which is important for immune regulation [9].…”
Section: Isoforms and Localizationmentioning
confidence: 99%
“…Na + /K + -ATPase uses almost 30 % of the ATP available to the cell and has important roles that include the following: (1) maintaining ionic balance, (2) providing energy through the coupled transport of nutrients, (3) re-establishing the ionic gradient after an action potential in neurons, (4) helping to maintain a gradient in epithelial cells, and (5) activating lymphocytes [9].…”
Section: Introductionmentioning
confidence: 99%
“…The 43-kDa ATP1B3, a β-subunit of Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/yviro ATPase, is localized to the q22-4 23 region of Chromosome (Chr) 3 (Besirli et al, 1998;Malik et al, 1998). Previous studies have demonstrated that ATP1B3 can up-regulate lymphocyte activity and promote the production of IFN-γ, IL-2, IL-4, and IL-10 (Chiampanichayakul et al, 2002) (Chruewkamlow et al, 2015). However, whether ATP1B3 can mediate the innate immune responses during EV71 infection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%